Multi-Tissue Methylation Clocks for Age and Sex Estimation in the Common Bottlenose Dolphin - Robeck, Todd R.; Fei, Zhe; Haghani, Amin; Zoller, Joseph A.; Li, Caesar Z.; Steinman, Karen J.; Dirocco, Stacy; Staggs, Lydia; Schmitt, Todd; Osborn, Steve; Montano, Gisele; Rodriguez, Magdalena; et al. (Frontiers in Marine Science, 2021)
Accurate identification of individual ages within wild bottlenose dolphins (Tursiops truncatus) is critical for determining population health and the development of population management strategies. As such, we analyzed DNA methylation patterns by applying a custom methylation array (HorvathMammalMethyl40) to both blood (n = 140) and skin samples (n = 87) from known age or approximate age (0 to 57 years) bottlenose dolphins. We present three bottlenose dolphin specific age estimation clocks using combined blood and skin (48 CpGs, R = 0.93, median absolute error = 2.13 years), blood only (64 CpGs, R = 0.97, error= 1.46 years) and skin only (39 CpGs, R = 0.95, error= 2.53). We characterize individual cytosines that correlate with sex and age in dolphins and developed a sex estimator based on 71 CpGs predicts the sex of any odontocete species with 99.5% accuracy. The presented epigenetic clocks are expected to be useful for conservation efforts and for determining if anthropogenic events effect aging rates in wild populations.